Association of glutamin and GLP-1 in inflammatory processes: scope review (Research, Society and Development, 2021)
Glutamine is the free amino acid abundant in plasma and muscle tissue. Nutritionally it is classified as a non-essential amino acid as it can be synthesized by the body from other amino acids. Glutamine is involved in different functions such as cell proliferation and development. Both aim to increase the half-life of circulating GLP-1 incretin (an important compound for the maintenance of glucose homeostasis). The administration of these drugs improves glycemic control by increasing insulin production and secretion in patients with type 2 diabetes. Previous studies have shown that glutamine is an amino acid with interesting effects preventing inflammation and cell apoptosis and exerting a beneficial effect. Methods and Analysis Using Arksey and O'Malley's scoping review methodology as a guide, the scoping review of published reviews begins by searching several databases: Search strategy and information source. For the selection of databases, coverage in the area of Health Sciences is considered, made available through the Capes Journal Portal and the Library System Portal of the Federal University of Paraná́ (UFPR). The selected databases are: PubMed, Cochrane Central Register of Controlled Trials (CENTRAL) at the Cochrane Library, Medline Complete (EbscoHost), Embase (Ovid), CINAHL (Cumulative Index to Nursing and Allied Health Literature), LILACS (BIREME), Web of Science,Virtual Health Library (VHL Regional Portal) and SCIELO. Bibliographic data and abstract content will be collected and analyzed by one of the research reviewers. Ethics and disclosure. This protocol reports a comprehensive, rigorous, transparent, and rigorous methodology. This is a review will be a pioneering study to analyze glutamine and Glp-1 in inflammatory processes. The results will be published through the literature, this study can guide.